Inferior mesenteric vein preserving lymphadenectomy in high left segmental colectomy for splenic flexure melanoma: A case report. (March 2023) - Crowe, Amy; Nasser, Ra; Seth, Ishith; Lee, Angus
Abstract: Introduction and importance: Surgical resection is the mainstay for management of splenic flexure cancers, with the aim of achieving adequate lymphadenectomy. Left-sided bowel resections often require ligation of the inferior mesenteric vein (IMV) for mesocolic dissection or lymphadenectomy which can result in congestive colitis on the anal side of the anastomosis secondary to poor venous outflow. Preserving the IMV may mitigate this risk but is technically difficult and can compromise oncological resection. This case report is a rare example of high left segmental resection of the splenic flexure with preservation of the IMV in a patient with splenic flexure melanoma. Case presentation: A non-obstructing lesion was discovered in a 73-year-old male who underwent colonoscopy following a positive faecal occult blood test. Biopsy of the lesion confirmed a melanoma. This patient had a history of cutaneous melanoma which was excised 20 years prior. A laparoscopic high left segmental colectomy was performed, and metastatic melanoma was identified in 3 of 12 regional lymph nodes. The patient recovered with no complications. Clinical discussion: This patient underwent high left segmental colectomy to achieve oncological clearance while resecting minimal bowel and preserving bowel function. The IMV was spared in this surgery to prevent venous congestion. Reports of colitis following left sided colectomy have been described, whereby colitis is thought to result from a mismatch in arterial perfusion and venous drainage following IMV resection. Conclusion: This case highlights the potential role of preservation of the inferior mesenteric vein in a rare case of splenic flexure melanoma. Highlights: Preservation of inferior mesenteric vein in left-sided colectomy is rare and adequate lymph node retrieval is important. Preservation of inferior mesenteric vein in left-sided colectomy allows to prevent congestion and colitis. Multi-disciplinary discussion for splenic flexure carcinomas are indicated.